On Certain Subclass of Harmonic Starlike Functions - A. Y. Lashin (Abstract and Applied Analysis)
Coefficient conditions, distortion bounds, extreme points, convolution, convex combinations, and neighborhoods for a new class of harmonic univalent functions in the open unit disc are investigated. Further, a class preserving integral operator and connections with various previously known results are briefly discussed.